Role of Outpatient Cardiac Rhythm Monitoring in Cryptogenic Stroke: A Systematic Review and Meta‐Analysis. Issue 10 (27th August 2015) - AFZAL, MUHAMMAD R.; GUNDA, SAMPATH; WAHEED, SALMAN; SEHAR, NANDHINI; MAYBROOK, RYAN J.; DAWN, BUDDHADEB; LAKKIREDDY, DHANUNJAYA
<x xml:space="preserve">Abstract</x> Background Recent studies have suggested that prolonged outpatient rhythm monitoring results in increased detection of atrial fibrillation (AF) in patients with cryptogenic stroke (CS). However, the best monitoring strategy and its clinical utility is debatable. Objective To compare the effectiveness of implantable loop recorder (ILR) versus wearable devices in identifying AF in patients with CS. Methods and Results Three randomized controlled trials (RCTs) and 13 observational studies were identified by database searches. Seven studies (enrolling 774 patients) employed ILR for AF detection for a median duration of 365 days (range 50–569 days). Ten studies (enrolling 996 patients) employed continuous monitoring with wearable devices for a median duration of 21 days (range 4–30 days). One study performed 7 days of monitoring with wearable device followed by implantation of ILR, thus included in both groups. Pooled odds ratio (OR) of identifying AF in RCTs showed increased detection of AF with prolonged monitoring (OR 4.54, 95% confidence interval [CI] 2.92, 7.06; P < 0.00001) compared to routine outpatient follow‐up. Overall detection of AF with outpatient monitoring was 17.6% (CI: 12.5–22.7). There was significantly higher AF detection with ILR (23.3%; CI: 13.83–32.29) compared to wearable devices (13.6%; CI: 7.91–19.32; P < 0.05). Patients with AF were older in age compared to patients without AF. Conclusion AF detection in patients with CS is improved with prolonged rhythm monitoring and is better with ILR compared to wearable devices. AF was more common in older patients. The clinical significance of these findings is unknown at this point.